2021
DOI: 10.1097/ijg.0000000000001859
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Angiography Vessel Density Changes in Normal-tension Glaucoma Treated With Carteolol, Brimonidine, or Dorzolamide

Abstract: Precis: In patients with normal-tension glaucoma (NTG), topical dorzolamide might enhance the vessel density (VD), topical carteolol decreased the VD in the inferior-temporal peripapillary retina, whereas topical brimonidine did not change the VD. Purpose: Topical antiglaucoma medications may improve ocular perfusion pressure or microcirculation in the optic nerve head. The study evaluated responses of retinal VD to topical carteolol, brimonidine, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
(47 reference statements)
1
12
0
Order By: Relevance
“… 31 More recent studies evaluated retinal perfusion after brimonidine application in patients with OHT and normal-tension glaucoma by OCTA, and found no evidence for a significant effect. 25 , 26 …”
Section: Discussionmentioning
confidence: 99%
“… 31 More recent studies evaluated retinal perfusion after brimonidine application in patients with OHT and normal-tension glaucoma by OCTA, and found no evidence for a significant effect. 25 , 26 …”
Section: Discussionmentioning
confidence: 99%
“…Peripapillary blood flow increased after treatment with either brinzolamide (111) or dorzolamide/ timolol (115). OCTA results have further demonstrated a peripapillary region VD increase after the topical application of either dorzolamide (110) or latanoprost (112). Although brimonidine may not cause a significant change in the microvascular VD (110), it has been reported to be correlated with improved microvascular autoregulation (89,90).…”
Section: Topical Medical Therapiesmentioning
confidence: 95%
“…However, some patients showed a decrease in the retinal blood flow after using topical carteolol ( 109 ). Lin et al used OCTA to detect a VD decrease in the inferior-temporal peripapillary region after topical carteolol use ( 110 ). Kurysheva observed a decrease in inside disc VD on OCTA after tafluprost administration ( 26 ).…”
Section: The Effect Of Glaucoma Treatment On Retinal Microvasculaturementioning
confidence: 99%
“…However, the findings pertaining to the effect of IOP reduction on microvascular change in patients with glaucoma are inconsistent. Some studies have revealed an improvement in OCT angiography parameters after IOP reduction treatment [ 7 , 8 , 9 , 10 , 11 ], whereas others have not [ 12 , 13 , 14 ]. Moreover, most studies have focused on the effect of surgical IOP reduction [ 10 , 11 , 13 , 14 ] instead of medical IOP reduction [ 7 , 8 , 15 ], which is the most common initial choice for treating glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have revealed an improvement in OCT angiography parameters after IOP reduction treatment [ 7 , 8 , 9 , 10 , 11 ], whereas others have not [ 12 , 13 , 14 ]. Moreover, most studies have focused on the effect of surgical IOP reduction [ 10 , 11 , 13 , 14 ] instead of medical IOP reduction [ 7 , 8 , 15 ], which is the most common initial choice for treating glaucoma. A prospective investigation of the changes in the ocular microvasculature induced by IOP-lowering medications may help to clarify the effect of long-term IOP reduction treatments on glaucoma.…”
Section: Introductionmentioning
confidence: 99%